2015
DOI: 10.1111/dote.12378
|View full text |Cite
|
Sign up to set email alerts
|

Topical hemostatic powder promotes reepithelialization and reduces scar formation after extensive esophageal mucosal resection

Abstract: The development of techniques for endoscopic resection has provided new strategies for radical conservative treatment of superficial esophageal neoplasms, even those that are circumferential, such as Barrett's neoplasia. However, it is necessary to prevent the formation of scar tissue that can be responsible for esophageal strictures following circumferential resection. Preliminary data have suggested the possible efficacy of a hemostatic powder in the promotion of wound healing. The study aims to assess the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In our study, however, quantitative measurements of serum pro‐inflammatory and profibrotic cytokines suggested that the application of CMC sheets on the mucosal defect had an antifibrotic action by downregulating the expression of TGF‐β1. This result was also similar to the effectiveness of hemostatic powder used in wound covering post‐ESD . Thus, we suppose that the different tissue‐shielding methods mentioned above which could reduce fibrosis may have the same result in downregulating serum TGF‐β1 levels because of biomaterial shielding.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our study, however, quantitative measurements of serum pro‐inflammatory and profibrotic cytokines suggested that the application of CMC sheets on the mucosal defect had an antifibrotic action by downregulating the expression of TGF‐β1. This result was also similar to the effectiveness of hemostatic powder used in wound covering post‐ESD . Thus, we suppose that the different tissue‐shielding methods mentioned above which could reduce fibrosis may have the same result in downregulating serum TGF‐β1 levels because of biomaterial shielding.…”
Section: Discussionsupporting
confidence: 75%
“…This result was also similar to the effectiveness of hemostatic powder used in wound covering post-ESD. 26 Thus, we suppose that the different tissue-shielding methods mentioned above which could reduce fibrosis may have the same result in downregulating serum TGF-b1 levels because of biomaterial shielding. Further tests are needed to prove this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal transplantation to the ESD wound is an effective and safe measure, but the technique remains underdeveloped and has cost implications [11]. Other preventive options for stricture mainly referring to local treatments of topical hemostatic powder and poly eth- anol acid membrane still lack sound evidence [12][13][14]. Furthermore, the interventions mentioned above have limited efficacy for the prevention of esophageal stricture after ESD.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent stricture formation after extensive endoscopic resection, the use of oral steroids, the endoscopic injection of steroids or topical application of hemostatic powder or polyglycolic acid sheets have recently been suggested 28 29 30 31 32. Although these techniques seem to be promising, none of the available preventive methods is efficient and safe enough to justify recommendation for routine use in clinical practice 33.…”
Section: Discussionmentioning
confidence: 99%